PRODUCT PLACEMENT ON THE VIRTUAL INFLUENCER’S INSTAGRAM TOWARDS BRAND RECALL - Cokki, Cokki; Putri, Angely Olivia; Tiffany, Fransisca; Wijaya, Santrista; Natalya, Yenny (International Journal of Application on Economics and Business, 2025)
This study aims to examine the influence of product placement on the virtual influencer’s Instagram account (@allysagladys) towards brand recall. The sample size for this study consists of 60 students from Tarumanagara University in West Jakarta. The method used in this study to collect the data is convenience sampling where questionnaires were distributed directly to the respondents. The results of this study shows that respondents brand recall is affected by product placement on the virtual influencer's account. Additionally, this study suggests that companies should enhance their social media promotion through collaborations with influencers to improve brand recall of their product.